Preservation of the personal papers of Prof. Raul Rafael Ingles, 1929-2013 - Abian, Gianina Alexea I. (School of Library and Information Studies, University of the Philippines, Diliman, 2018)
The special project documented the preservation activities done to the personal papers of Prof. Raul Rafael Ingles. Activities such as records consolidation, records selection and appraisal, records preservation and storage, and formulation of the finding aids and file plan were conducted and considered as the main tasks involved in this project. Approximately six (6) linear feet of records and paper ware arranged and classified using the file-level description of archival documents. The classified documents were placed in corrugated file boxes to increase its longevity and posterity.